Italy : Staff Report for the 2004 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
This 2004 Article IV Consultation highlights that a cyclical recovery is under way for Italy, with real GDP having risen by 1.2 percent in the first three quarters of 2004 relative to the same period of the previous year, thanks to the favorable external environment and a recovery of investment. A package of corrective measures adopted in mid-2004 is likely to have proven sufficient to keep the fiscal deficit just below 3 percent of GDP last year. IMF staff forecasts growth of 1.5 percent in 2004 and 1.7 percent in 2005.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet